Dot coms bounce back - Miller, Charles; BBC Active ([United Kingdom] : BBC Active, 2006)
With the stock market flotation of internet search engine Google.com expected to make its young founders billionaires, there are signs that the dot coms are bouncing back, but will the new confidence in the tech market last longer this time? This program will give the answer
Title from title screen
Camera : Charles Miller ; sound : Helen Britton ; graphics : Pryce Duncalf
Narrator : Rajan Datar
Keywords: Electronic commerce; Internet; Business enterprises -- Computer networks